All-Optical NOT Gate Based on Nanoring Silver-Air Plasmonic Waveguide - Falah Fakhruldeen, Hassan; Safaa Mansour, Tahreer (International Journal of Engineering and Technology, 2018)
In this work, all-optical plasmonic NOT logic gate was proposed by using metal-insulator-metal (MIM) plasmonic waveguides design. This logic gate is numerically analyzed by COMSOL Multiphysics 5.3a. Recently, plasmonics have attracted more attention due to its huge applications in all optical signal processing. Due to itâ€™s highly localization to metallic surfaces, surface plasmon (SP) may have many applications in sub wavelength to guide the optical signal in waveguides to overcome the diffraction limit which considered a big problem in conventional optics. The proposed design of MIM structure is consist of a dielectric waveguides plus metallic claddings, which guide the incident light strongly in the insulator region. Strong localization and relatively simple fabrication make the MIM waveguides the potential key design of Nano-scale all optical devices. Our design consists of symmetric ring structures with straight waveguides which based on MIM structure. All-optical logic gate (NOT gate) behavior is achieved from utilizing the interface between straight waveguides and ring structure waveguides. By switching the activation of the control port, the propagation of the outgoing field in the output waveguide will be changed. As the simulation results show, the proposed structure could operate as an all-optical NOT logic gate. This gate would be a potential component in many applications of all-optical signals processing.Â Â